“Freeze, Don’t Move”: How to Arrest a Suspect in Heart Failure – A Review on Available GRK2 Inhibitors - Sorriento, Daniela; Ciccarelli, Michele; Cipolletta, Ersilia; Trimarco, Bruno; Iaccarino, Guido (Frontiers in Cardiovascular Medicine, 2016)
Cardiovascular disease and heart failure (HF) still collect the largest toll of death in western societies and all over the world. A growing number of molecular mechanisms represent possible targets for new therapeutic strategies, which can counteract the metabolic and structural changes observed in the failing heart. G protein-coupled receptor kinase 2 (GRK2) is one of such targets for which experimental and clinical evidence are established. Indeed, several strategies have been carried out in place to interface with the known GRK2 mechanisms of action in the failing heart. This review deals with results from basic and preclinical studies. It shows different strategies to inhibit GRK2 in HF in vivo (βARK-ct gene therapy, treatment with gallein, and treatment with paroxetine) and in vitro (RNA aptamer, RKIP, and peptide-based inhibitors). These strategies are based either on the inhibition of the catalytic activity of the kinase (“Freeze!”) or the prevention of its shuttling within the cell (“Don’t Move!”). Here, we review the peculiarity of each strategy with regard to the ability to interact with the multiple tasks of GRK2 and the perspective development of eventual clinical use.